Global Beauty, Local Bodies
XXV, 185 p. 3 illus.
Keywords: This collection of original scholarly work and first-person accounts takes globalization processes and the transnational links these processes create as the jumping-off point for an examination of what it means to be, have, or aspire to a beautiful body.